Critical language awareness as a future imperative: seeing the ‘water’ - Darics, Erika; Staschen, Orrie; Drury, Matt; Chojnicka, Joanna; Mazzoli, Maria; Olthof, Jelte; Serafis, Dimitris; Wildfeuer, Janina (Frontiers in Communication, 2025)
This position paper argues that critical language awareness (CLA) must be recognised as a core, future-oriented metacognitive competency. In our time marked by epistemic instability, discursive overload, and interconnected global crises, it is no longer sufficient for people to decode language; they must be equipped to question it, redesign it, and use it ethically to shape more just and sustainable futures. In this paper we review key disciplinary traditions concerned with the power of language and multimodal communication, including critical literacy, rhetoric, sociolinguistics, critical discourse studies, and ecolinguistics. Despite conceptual differences, we identify strong convergences: all treat language as constitutive of social realities and all call for awareness as a form of agency. Building on this shared ground, we propose a unified agenda for CLA that connects theory, practise, and transformation. We outline a new scope and five dimensions of CLA and frame it as a means of developing not only critical awareness, but communicative agency, advocacy, and activism. Scholars and educators can realise CLA’s potential by theorising, teaching, communicating, and operationalising it across disciplines and institutions. We argue that it is time to ‘see the water’: to make visible the linguistic forces that shape our world, and equip learners, educators, and citizens to reshape them.